Pengaruh Zat Pengatur Tumbuh Atonik Dan Pupuk Bokasi Terhadap Pertumbuhan Dan Hasil Tanaman Tomat (Solanum lycopersicum L.) - I Komang Sujana; Made Suarta; Ketut Agung Sudewa (GEMA AGRO, 2024)
This study aims to determine the interaction of Bokasi Fertilizer and Atonic Growth Regulators on the growth of tomato plants. This research was conducted in the greenhouse of the Faculty of Agriculture, Warmadewa University, JI. Ompong 24 Tanjung Bungkak, Denpasar with a height of 25 m above sea level. This research starts from August - October 2023. This experiment uses a factorial pattern Group Randomized Design (RAK) with two factors, namely: Factor I is atonic ZPT with 4 levels of concentration, namely: A0 = 0 cc 1-1, A1 = 1 cc 1-1, A2 = 2 cc 1-1, A3 = 3 cc 1-1, Factor II is bokashi fertilizer consisting of 4 concentrations, namely: B0= 0 tons / ha, B1 = 10 tons / ha, B2 = 20 tons / ha, B3 = 30 tons / ha, Thus there are 16 combination treatments, each of which is repeated 3x so that there are 48 experimental polybags. The treatment of atonic growth regulators 1 cc 1-1 tends to give the highest dry weight yield of 148.68 grams, which is not real from other treatments. The treatment of 30 tons / ha of bokasi fertilizer tends to produce the highest dry weight of 149.44 grams which is not real from other treatments. Bokasi fertilizer has a real effect (P<0.05) on the fruit diameter and no real effect (P>0.05) on other variables. The treatment of bokasi fertilizer of 30 tons / ha produces the highest fruit diameter of 3.49 cm which is not real with the treatment of fertilizer 0 tons / ha and 20 tons / ha with fruit diameters of 3.31 cm and 3.40 cm respectively, but differs markedly from the application of bokasi fertilizer of 10 tons / ha with a fruit diameter of 3.10 cm. Bocation fertilizer tends to show no real influence on the growth and yield of tomato plants which is likely due to goat manure bokashi fertilizer has not been absorbed by tomato plants optimally.